Health, Cognition and Work Capacity Beyond the Age of 50 - Vincent Vandenberghe (Global Labor Organization (GLO), 2019)
The rising cost of old-age dependency in Europe and elsewhere invariably leads to reforms aimed at raising the effective age or retirement. But do older individuals have the health/cognitive capacity to work longer? Following Cutler et al. (2012), this paper asks how much older individuals could work if they worked as much as their younger (50-54) counterparts in similar health/with equal cognitive performance. Contrary to existing papers, this one uses international, European, comparable panel evidence available in the Survey of Health, Ageing and Retirement in Europe (SHARE). It considers both physical health and cognition; and health consists of subjective and objective measures. Also, it examines the extensive and intensive margins of work (employment and hours): existing papers only consider the former. Results are essentially fivefold. First, declines in health significantly affect employment. Second, the impact on hours is statistical significant but of much smaller magnitude. People suffering from ill health rarely adjust hours; they rather stop working altogether. Third, cognition is not fundamentally affected by ageing, and it adds little to our capacity to predict how work capacity evolves with age. Fourth, identification issues exist and must be addressed. They comprise unobserved heterogeneity across respondents, justification bias or proxying/measurement errors regarding health. Finally, declining health/cognition explain at most 31% of the actual labour supply reduction between 50 and 70. This confirms the existence of a, currently largely underused, work capacity among older individuals.
Keywords: J22; I10; J26; 330; Ageing; Health; Cognition; Labour Supply; Work Capacity